Quality of life after intensive care: a systematic review of the literature - Oeyen, Sandra G; Vandijck, Dominique M; Benoit, Dominique D; Annemans, Lieven; Decruyenaere, Johan M (Critical care medicine, 2010)
To evaluate quality of life at least 12 months after discharge from the intensive care unit of adult critically ill patients, to evaluate the methodology used to assess long-term quality of life, and to give an overview of factors influencing quality of life. EMBASE-PubMed, MEDLINE (OVID), SCI/Web of Science, the Cochrane Library, Google Scholar, and personal files. Data extraction was performed independently and cross-checked by two reviewers using a predefined data extraction form. Eligible studies were published between 1999 and 2009 and assessed quality of life ≥12 months after intensive care unit discharge by means of the Medical Outcomes Study 36-Item Short Form Health Survey, the RAND 36-Item Health Survey, EuroQol-5D, and/or the Nottingham Health Profile in adult intensive care unit patients. Fifty-three articles (10 multicenters) were included, with the majority of studies performed in Europe (68%). The Medical Outcomes Study 36-Item Short Form Health Survey was used in 55%, and the EuroQol-5D, the Nottingham Health Profile, the RAND 36-Item Health Survey, or a combination was used in 21%, 9%, 8%, or 8%, respectively. A response rate of ≥80% was attained in 26 studies (49%). Critically ill patients had a lower quality of life than an age- and gender-matched population, but quality of life tended to improve over years. The worst reductions in quality of life were seen in cases of severe acute respiratory distress syndrome, prolonged mechanical ventilation, severe trauma, and severe sepsis. Study quality criteria, defined as a baseline quality of life assessment, the absence of major exclusion criteria, a description of nonresponders, and a comparison with a reference population were met in only four studies (8%). Results concerning the influence of severity of illness, comorbidity, preadmission quality of life, age, gender, or acquired complications were conflicting. Quality of life differed on diagnostic category but, overall, critically ill patients had a lower quality of life than an age- and gender-matched population. A minority of studies met the predefined methodologic quality criteria. Results concerning the influence of the patients' characteristics and illnesses on long-term quality of life were conflicting.